Analisis Kesehatan Keuangan Keluarga di Desa Puseurjaya Kabupaten Karawang - Syaprizal Hakiki; Wanta Wanta; Asep Darojatul Romli (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze family understanding of household financial health and to identify the application of family financial management in household budgeting in Puseurjaya Village, Telukjambe Timur District, Karawang Regency. The method used is a descriptive qualitative approach with data collection techniques consisting of in-depth interviews, observation, and documentation involving 10 informants comprising household heads and housewives. Data validation was carried out through source triangulation and method triangulation. The results show that 80% of informants have not comprehensively understood the concept of family financial health, while only 20% have understood and been able to apply it in daily life. No family was found to systematically record their finances. The application of financial management is still oriented toward short-term needs fulfillment, resulting in unhealthy household cash flows. The main factors behind low understanding and application of financial management include low formal education levels, lack of education from the village government, and limited public interest. Recommended improvement efforts include enhancing financial literacy, implementing household recording and budgeting systems, developing saving habits, practicing healthy debt management, and optimizing the role of the village government and local financial institutions.